Correlative Microscopy: Hybrid Nanoscopy of Hybrid Nanomaterials (Small 17/2017). Issue 17 (2nd May 2017) - Bondia, Patricia; Jurado, Rocío; Casado, Santiago; Domínguez‐Vera, José M.; Gálvez, Natividad; Flors, Cristina
Abstract : In article number1603784, by Natuvudad Gálvez, Cristina Flors, and co‐workers, the combination of complementary techniques to characterize materials at the nanoscale is explored, as a key step to the design and fabrication of new materials with improved properties and diverse functions. The combination of atomic force microscopy and super‐resolution fluorescence imaging is investigated as a useful tool to characterize hybrid luminescent materials, specifically amyloid‐like fibers functionalized with quantum dots.